Patient Experience of Chronic Inflammatory Demyelinating Polyneuropathy (CIDP): A Qualitative Exploration of Signs, Symptoms, and Health-Related Quality of Life Impacts - Anna Roberts; Natasha Griffiths; Kieran Thiara; Sophie Wallace; Alyson L. Young; Nicola Williamson; Adam Gater; Omar Saeed; Charles Minor; Natalia Hawken (Neurology and Therapy)
Abstract Introduction Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare type of autoimmune neuropathy, characterized by signs of distal and proximal weakness of the upper and lower limbs, sensory dysfunction, absent or diminished tendon reflexes, and symptoms of numbness, tingling, pain, and fatigue. These signs/symptoms can lead to difficulty walking, climbing stairs, and reduced manual dexterity. Detailed qualitative exploration of the patient experience of CIDP, notably signs/symptoms, its impacts on health-related quality of life, and treatment experience is limited. Qualitative patient experience data is recommended by regulatory bodies to inform patient-focused drug development. This study aimed to qualitatively explore the experience of CIDP from the patient and clinician perspectives. Methods Qualitative concept elicitation telephone interviews were conducted with adult patients with a confirmed diagnosis of CIDP and with neurologists experienced in diagnosing and treating patients with CIDP from the USA. Interview transcripts were analyzed using thematic analysis methods, and findings informed development of a conceptual model. Results Overall, 15 patients with CIDP and 10 neurologists were interviewed. A total of 19 signs/symptoms were identified as important and relevant, of which weakness, fatigue, loss of balance, tingling, numbness, pain, and loss of coordination were most frequently reported by patients and neurologists. Except for loss of coordination, these signs/symptoms were also considered most salient to patients. Patients identified fatigue as the most bothersome symptom and weakness and fatigue as the most important to treat. CIDP impacted health-related quality-of-life (HRQoL), including physical functioning (e.g., walking difficulties), activities of daily living (e.g., difficulty with personal care), work (e.g., being unable to work), emotional wellbeing (e.g., depression), social wellbeing (e.g., participation in social/leisure activities), sleep (e.g., difficulty falling asleep), and cognition (e.g., brain fog). Patients reported that current CIDP treatments lacked effectiveness in treating specific symptoms, caused unwanted side effects, and impacted their independence. Conclusions Findings contribute novel and detailed qualitative insights into the key signs/symptoms of CIDP and the profound impact of these on patients’ HRQoL from both the patient and clinician perspectives. Findings can be used to identify treatment targets and support selection of appropriate clinical outcome assessments for the evaluation of CIDP symptoms and HRQoL impacts in future CIDP clinical trials.